Influence of Stage of Change, Self-Efficacy and Socio-Economic Factor on Dietary Fat Intake Behavior among Saudi Women - Al Otaibi, Hala Hazam (Pakistan Journal of Nutrition, 2011)
Diet high in fat contributes significantly to development of major chronic diseases. The purpose of this study was to examine the influence of stage of change, self-efficacy and socio-economic factors on dietary fat intake behavior among university employee’s women in Saudi Arabia. A total 74 non-academic staff aged 23-52 years in of King Faisal University participated in the study. A pre-tested interview questionnaire was used to measure socio-economic, stages of change and self-efficacy related to dietary fat intake, also anthropometric measurement, total energy and dietary fat intake were determined. Chi square test, one way analysis of variance and multiple regression analysis were used for data analysis. Results showed that about 20% of subjects reduce their daily fat intake and more than two-third of subjects (67.5%) intend to change. There were significant differences between stages of change for dietary fat and energy from fat (F = 6.57-7.64, respectively; p = 0.00) and significant association between stages of change and age (p = 0.014). The anthropometric measurement did not differ significantly by stages. Stages of change (p = 0.00) and self-efficacy (p = 0.044) were the most relevant predictor for dietary fat intake. This study revealed important relationship between stage of change, self-efficacy and dietary fat intake, which is useful insight for health professionals and nutrition educators to explore other target groups in the community and to design effective intervention.